2022
DOI: 10.3390/coatings12030409
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Cu-MWCNT Nanocomposites Manufactured by Powder Technology

Abstract: This paper presents an experimental investigation of the fabrication of Cu–multi-walled carbon nanotube (MWCNT) nanocomposites prepared via the electroless chemical deposition technique followed by the powder metallurgy (PM) method. To enhance the dispersion and wettability of MWCNTs with a Cu matrix, MWCNTs were given an electroless coating of Ag nanoparticles. MWCNTs with 0.4, 0.8, and 1.2 wt.% were first coated with 5 wt.% Ag nanoparticles, then mechanically milled with Cu nanoparticles using a 10:1 ball-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In support of these observations, Shao et al reported that a nanocomposite coating synthesized from hydroxylated MWCNTs and Cu via electrodeposition exhibited superior anticorrosion properties [25]. The anticorrosion properties of MWCNTs/Cu epoxy on the steel substrate are related to the addition of Cu and MWCNTs [26,27]. Shukla et al [28] fabricated Cu/CNT composites using the vacuum hot pressing method.…”
Section: Introductionmentioning
confidence: 94%
“…In support of these observations, Shao et al reported that a nanocomposite coating synthesized from hydroxylated MWCNTs and Cu via electrodeposition exhibited superior anticorrosion properties [25]. The anticorrosion properties of MWCNTs/Cu epoxy on the steel substrate are related to the addition of Cu and MWCNTs [26,27]. Shukla et al [28] fabricated Cu/CNT composites using the vacuum hot pressing method.…”
Section: Introductionmentioning
confidence: 94%
“…Modeling thermal stresses and heat transfer in materials with temperaturedependent thermophysical properties is a cumbersome problem [2][3][4]. Reinforcing metals or polymers with nano additives produces nanocomposites with enhanced properties [5][6][7][8][9]. The enhanced mechanical and tribological properties of these nanocomposites make them 2 of 16 an excellent choice for different engineering applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing attention has been paid to nitride coatings with multilayer architecture due to their high mechanical and tribological characteristics [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The multilayer architecture of the obtained coatings makes it possible to influence the structural-phase state of the layers by changing the modulation period of alternating layers, and, in addition, allows for combining their individual properties [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%